QTL mapping of 1000-kernel weight, kernel length, and kernel width in bread wheat (Triticum aestivum L.) - Ramya, P.; Chaubal, A.; Kulkarni, K.; Gupta, L.; Kadoo, Narendra Y.; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Lagu, Meena D.; Gupta, V. (Journal of Applied Genetics, 2010)
Kernel size and morphology influence the market value and milling yield of bread wheat (Triticum aestivum L.). The objective of this study was to identify quantitative trait loci (QTLs) controlling kernel traits in hexaploid wheat. We recorded 1000-kernel weight, kernel length, and kernel width for 185 recombinant inbred lines from the cross Rye Selection 111 x Chinese Spring grown in 2 agro-climatic regions in India for many years. Composite interval mapping (CIM) was employed for QTL detection using a linkage map with 169 simple sequence repeat (SSR) markers. For 1000-kernel weight, 10 QTLs were identified on wheat chromosomes 1A, 1D, 2B, 2D, 4B, 5B, and 6B, whereas 6 QTLs for kernel length were detected on 1A, 2B, 2D, 5A, 5B and 5D. Chromosomes 1D, 2B, 2D, 4B, 53 and 5D had 9 QTLs for kernel width. Chromosomal regions with QTLs detected consistently for multiple year-location combinations were identified for each trait. Pleiotropic QTLs were found on chromosomes 2B, 2D, 4B, and 5B. The identified genomic regions controlling wheat kernel size and shape can be targeted during further studies for their genetic dissection.
Keywords: composite interval mapping; kernel shape; kernel size; quantitative trait loci; Stable QTLs; Triticum aestivum

Kernel morphometric traits in hexaploid wheat (Triticum aestivum L.) are modulated by intricate QTL x QTL and genotype x environment interactions - Prashant, Ramya; Kadoo, Narendra Y.; Desale, Charushila; Kore, Prajakta; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Gupta, Vidya (Journal of Cereal Science, 2012)
Wheat kernel size and shape influence its flour yield and market price. A hexaploid wheat population of 185 recombinant inbred lines was evaluated for five kernel morphometric traits namely, 1000-kernel weight, kernel length, width, length width ratio and factor form density in two diverse agro-climatic regions in India in five to eight year location combinations. Additive main effects and multiplicative interaction analysis revealed significant contributions from genotype (G) and genotype x environment (G x E) effects for these traits. Quantitative trait locus (QTL) analysis by composite interval mapping (CIM) was performed using a linkage map of 251 SSR markers and 59 QTLs distributed on 16 chromosomes were identified. The majority of the QTLs were located on the D genome (44.07%) and the homeologous chromosomes of Group 2 (38.98%). Stable QTLs detected in three or more year location combinations were identified for four traits. Multi-trait CIM showed 10 chromosomal regions harboring putative pleiotropic loci. Complexity in the genetic effects was further revealed by QTL analysis based on mixed-linear model that indicated 19 QTLs with significant individual effects (main-effect QTLs) and 14 QTL x QTL interactions. Five of these - nineteen main-effect QTLs and one of the fourteen QTL x QTL interactions showed environmental influence. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Epistatic QTLs; Genotype x environment interactions; Kernel size and shape; Stable QTLs